Modeling the photoperiodic entrainment of the plant circadian clock. (7th May 2017) - De Caluwé, Joëlle; de Melo, José Romário Fernandes; Tosenberger, Alen; Hermans, Christian; Verbruggen, Nathalie; Leloup, Jean-Christophe; Gonze, Didier
Abstract: The circadian clock is an endogenous 24 hour rhythm that helps organisms anticipate and adapt to daily and seasonal variations in environment, such as the day/night cycle or changing temperatures. The plant clock is a complex network of transcription factors that regulate each other, forming interlocked feedback loops. Most of its components are light-regulated in some way, making the system highly sensitive to changes in light conditions. Here, we explore the mechanisms by which the plant clock adapts to changing day length. We first present some experimental data illustrating the variety of behaviors found in seedlings exposed to external day/night cycles different from 24 h. We then use a mathematical model to characterize the response of the clock to a wide range of external cycle lengths and photoperiods. We show the existence of several domains of periodic entrainment with different ratios between the external cycle length and the period of the clock, and the presence of quasiperiodic and chaotic behaviors outside of the entrainment range. We simulate knockout mutants with impaired clock function and theoretical variants with diminished light sensitivity to highlight the role of a complex network and multiple light inputs in keeping the clock entrained over a wide range of conditions. Abstract : Graphical abstract: Abstract : Highlights: A mathematical model suggests that the plant clock can be entrained by non-24 h cycles. Large domains of periodic entrainment are surrounded by chaos and quasiperiodicity. Multiple light inputs and a complex network confer flexibility to the clock.